Solvothermal liquefaction of waste polyurethane using supercritical toluene in presence of noble metal catalysts. Issue 12 (27th August 2022) - Ghalandari, Vahab; Banivaheb, Soudeh; Peterson, Jessica; Smith, Hunter; Reza, M. Toufiq
Abstract: Solvothermal liquefaction (STL) is a thermochemical conversion method that uses sub‐or supercritical solvents to convert waste plastics like waste polyurethane (PU) into value‐added chemicals. This study aimed to evaluate catalytic STL utilizing toluene as a solvent for depolymerization of waste PU into valuable products. The effect of catalyst type (Pt/C, Pd/C, and Ru/C), catalyst loading (0–10 wt%), STL reaction temperature (330°C, 350°C, and 370°C), STL residence time (1, 3, and 5 h), and hydrogen loading (25, 50, and 75 bar) on STL conversion were studied. Results showed that Ru/C outperformed Pt/C and Pd/C and the STL conversion reached to as high as 87.2%. The concentrations of nitrogen‐containing components like aniline and p‐aminotoluene were increased with the increase of Ru/C loading and STL reaction temperature.